Ciencia, revolución y nacimiento de la sociología. (2017)
The École Polytechnique was an academic, revolutionary and scientific institution founded at the end of the 18th century in France. The school brought together the leading scientists of the time and used revolutionary principles to establish the profession of engineer, the current concept of the scientific community and the modern link between knowledge and the state apparatus. Within the educational institution sociology emerged as a science, under a positivist conception. In this article we analyze the close links between the creation of the École Polytechnique and its importance in the birth of sociology.